PENDAMPINGAN PENINGKATAN KOMPETENSI KOMUNITAS PENGELOLA JURNAL LPTNU PCNU NGANJUK MENUJU JURNAL NASIONAL TERAKREDITASI - Edi Nurhidin (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This study focuses on mentoring strategies for Nganjuk Regency LPTNU PCNU journal managers. This strategy has two main orientations: increasing the competence of journal managers and accrediting the journals being managed. This study uses the participatory action research (PAR) method because both orientations are forms of fundamental social transformation. This study found that the management of the journal